2005
DOI: 10.1503/cmaj.1040432
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of severe trauma among status Aboriginal Canadians: a population-based study

Abstract: Background: Aboriginal Canadians are considered to be at increased risk of major trauma. However, population-based studies characterizing the distribution, determinants and outcomes of major trauma in this group are lacking. We sought to measure the impact of ethnicity, as reflected by Aboriginal status, on the incidence of severe trauma and to broadly define the epidemiologic characteristics of severe trauma among sta-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
74
0
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 10 publications
(6 reference statements)
1
74
0
6
Order By: Relevance
“…While injuries are known to be one of the leading causes of death in Canada, Aboriginal populations are especially at risk; however, as mentioned previously, there are few studies that have explored this trend (Karmali et al 2005). Waldram, Herring, and Young (2006) noted that injuries are responsible for 25 percent of deaths in First Nations populations, while injuries account for less than 10 percent of deaths in non-Aboriginal populations.…”
Section: Injury Rates For Aboriginal Peoplesmentioning
confidence: 99%
“…While injuries are known to be one of the leading causes of death in Canada, Aboriginal populations are especially at risk; however, as mentioned previously, there are few studies that have explored this trend (Karmali et al 2005). Waldram, Herring, and Young (2006) noted that injuries are responsible for 25 percent of deaths in First Nations populations, while injuries account for less than 10 percent of deaths in non-Aboriginal populations.…”
Section: Injury Rates For Aboriginal Peoplesmentioning
confidence: 99%
“…The same study found that sexual abuse increased the risk of sexually transmitted infections (STIs) and number of lifetime sexual partners. Simoni, Sehgal, and Walters (2004) Aboriginal people in Canada appear to have greater vulnerability to traumatic life events compared to non-Aboriginal people (Karmali et al, 2005), including sexual abuse (Hylton, 2002). However, there is a paucity of research addressing the relationship between sexual trauma and risk for HIV infection among young Aboriginal people in Canada.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] A number of studies have shown that the suicide rates within First Nations youth are alarmingly high; however, little research has examined suicide ideation in this group, nor the extent to which different factors contribute to suicidal thoughts or attempts. 9 Victims of bullying in children and adolescence are also recognized as being at increased risk for suicidal ideation. 10 Bullying can take various forms, 11 traditionally including physical (e.g., assault), verbal (e.g., threats), relational bullying (e.g., social exclusion) and more recently, electronic bullying (e.g., e-mail, phone).…”
mentioning
confidence: 99%